GROWTH AND YIELD COMPONENTS OF WHEAT (TRITICUM AESTIVUM L.) VARIETIES AS INFLUENCED BY SOWING INTERVALS IN SOUTH-EASTERN NIGERIA - Otie, V.O.; Udo, I.I.; Unagwu, B.O.; Onwudiwe, N.; Nwandu, C.G.; Afu, S.M.; Udo, I.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The research was conducted to determine the effects of different sowing intervals (SIs) on growth and yield of some wheat varieties under Southern-Nigeria’s climatic conditions. The treatments consisted of four (4) varieties of wheat (Imam, Sc. Sahai, Norman and WZ 273 2015) and three (3) sowing intervals (5th December, 2024; 5th January and 5th February, 2025). These were factorially combined and laid out in a completely randomized design and replicated three times. Growth, physiological and yield variables were measured. The result revealed that, sowing wheat on 5th December recorded the highest growth compared with other SIs (5th January and February). Variety on the other hand, imam was better in growth traits and optimized more (p≤0.05) photosynthesis at 8 WAS whereas WZ 273 2015 was higher in photosynthetically active radiation at 4 and 6 WAS. Sc.Sahai significantly took fewer (55.71) number of days to heading relative to other varieties. WZ 273 2015 had longer (p≤0.05) spike length when sown on 5th December, as well as number of spikelets/main spike and spike weight. Sowing wheat on 5th December resulted in significantly higher dry matter and yield viz., plant’s dry weight, number of grains/plant and grain weight/plant, especially in Norman and WZ 273 2015, relative to other SIs. Imam consistently performed better in growth traits, whereas WZ 273 2015 and Norman were stable in yield components and grain yield. Overall, 5th December was a more suitable timing than other SIs, as it recorded better performance among the varieties. Based on the result of this study, cultivating wheat in Calabar could be sustainable in the early part of December, which is subject to further investigation.